Oral hydroxysafflor yellow A reduces obesity in mice by modulating the gut microbiota and serum metabolism. (August 2018) - Liu, Juan; Yue, Shijun; Yang, Zhirui; Feng, Wuwen; Meng, Xintong; Wang, Aiting; Peng, Cheng; Wang, Changyun; Yan, Dan
Graphical abstract: Abstract: Given the high and increasing prevalence of obesity, the safe and effective treatment of obesity would be beneficial. Here, we examined whether oral hydroxysafflor yellow A (HSYA), an active compound from the dried florets of Carthamus tinctorius L., can reduce high-fat (HF) diet-induced obesity in C57BL/6 J mice. Our results showed that the average body weight of HF group treated by HSYA was significantly lower than that of the HF group (P < 0.01). HSYA also reduced fat accumulation, ameliorated insulin resistance, restored glucose homeostasis, reduced inflammation, enhanced intestinal integrity, and increased short-chain fatty acids (SCFAs) production in HF diet-fed mice. Sequencing of 16S rRNA genes in fecal samples demonstrated that HSYA reversed HF diet induced gut microbiota dysbiosis. Particularly, HSYA increased the relative abundances of genera Akkermansia and Romboutsia, as well as SCFAs-producing bacteria, including genera Butyricimonas and Alloprevotella, whereas it decreased the phyla Firmicutes/Bacteroidetes ratio of HF diet-fed mice. Additionally, serum metabolomics analysis revealed that HSYA increased lysophosphatidylcholines (lysoPCs), L-carnitine and sphingomyelin, and decreased phosphatidylcholines in mice fed a HF diet, as compared to HF group. These changed metabolites were mainly linked with the pathways of glycerophospholipid metabolism and sphingolipid metabolism. Spearman's correlation analysis further revealed that Firmicutes was positively while Bacteroidetes and Akkermansia were negatively correlated with body weight, fasting serum glucose and insulin. Moreover, Akkermansia and Butyricimonas had positive correlations with lysoPCs, suggestive of the role of gut microbiota in serum metabolites. Our findings suggest HSYA may be a potential therapeutic drug for obesity and the gut microbiota may be potential territory for targeting of HSYA.